(untitled) (JÓVENES EN LA CIENCIA, 2021)
This article reports on a case study of the effects of collective accompaniment and collaborative reflection on the pedagogic beliefs of an English as a Foreign Language teacher. Following the Collective Accompaniment Model (CAM) (Guillemette, 2014), a group of eight English instructors took part in a bi-weekly series of group sessions aimed at helping them discover and understand their beliefs about teaching and learning through collective reflection. After this process concluded, Kelly’s (1955) Repertory Grid Technique (RGT) was used for the collection of data. For the purposes of the current study, one participant’s pre- and post-interviews were analyzed in order to better understand the effects of CAM sessions on her pedagogical beliefs.